Web-based multimedia learning of arabic vocabulary pronunciation / Nur Shazlena Sarif Puddin - Sarif Puddin, Nur Shazlena (2020)
Arabic vocabulary is one important knowledge in learning Arabic learning. It can help Muslims to understand the content of Al-Quran. Some people found that Arabic vocabulary is difficult and confusing in order to get caught of the knowledge. On the other hand, learners faced difficulties in learning Arabic vocabulary, especially the pronunciation due to limited hours of learning in the class and less attractive of teaching materials. Thus, this study is aimed to identify the current approach and the problems in the web-based multimedia learning of Arabic vocabulary pronunciation. This project also aims to design and develop web-based multimedia learning of Arabic vocabulary pronunciation. This system has been evaluated and tested by UiTM students using User Acceptance Test (UAT). For the development, the researcher has developed this web-based multimedia learning based on System Development Life Cycle (SDLC) as the methodology that consists of six phases, which are planning, information gathering, analysis, implementation and testing. In each phase, the activities, techniques or software used, and the deliverables have been determined by the researcher. Web-based multimedia learning of Arabic vocabulary pronunciation is evaluated using Expert Review by distributing questionnaires among five experts and User Acceptance Test (UAT) contributed thirty students in UiTM Perlis. The result from the Expert Review shows that the system is suitable to use but still needs improvement. Meanwhile, the results from the User Acceptance Test indicated that the web-based multimedia learning of Arabic vocabulary pronunciation is efficient and helpful.